Penerapan Pendekatan Pembelajaran Berbasis Science, Environment, Technology, And Society (SETS) pada Meteri Zat Aditif pada Makanan di Kelas VIII SMPN 15 Banda Aceh - Fitri B. Menalu; . Sulastri; Latifah Hanum (Jurnal Ilmiah Mahasiswa Pendidikan Kimia, 2018)
ABSTRACTA research study entitled "Application of Science Environment Technology and Society (SETS) based learning approach on Food Additives Matter in Class VIII SMPN 15 Banda Aceh". The purpose of this study was to analyze the students 'early understanding of additives, to describe learners' activities during the learning process using SETS approach, to analyze students 'learning outcomes after the SETS approach was applied and to analyze the learners' responses to the learning using SETS approach. The type of research conducted in this research is quantitative research with descriptive method. The sample of this study students class VIII-1, amounting to 21 people consisting of 7 women and 14 men. Data collection techniques in this study by way of questionnaire initial understanding of learners about additive substances, observation of learning activities of learners, learning outcomes and questionnaire responses of learners to the application of SETS approach. The instrument used in this research is the questionnaire of students' initial understanding about additive, activity observation sheet, LKPD, test question and questionnaire of student's response to SETS approach. Early understanding of the students about additive is still in low category, especially sub topic on the characteristics of additives. The average result of observation of the students activity as a whole is 80.5%. The results showed the results of students' learning mastery of 87.62% .. The results of classical positive student responses to the teaching-learning process with the application of SETS approach of 85.03%.Keywords: learning outcomes, additives, SETS approach.ABSTRAKTelah dilakukan penelitian untuk menganalisis pemahaman awal peserta didik tentang zat aditif, mendeskripsikan aktivitas peserta didik selama proses pembelajaran menggunakan pendekatan SETS, menganalisis hasil belajar peserta didik setelah diterapkan pendekatan SETS dan menganalisis respon peserta didik terhadap pembelajaran menggunakan penerapan pendekatan SETS. Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif. Sampel penelitian adalah peserta didik kelas VIII-1 yang berjumlah 21 orang terdiri dari 7 orang perempuan dan 14 orang laki-laki. Instrumen yang digunakan dalam penelitian ini adalah lembar angket pemahaman awal peserta didik tentang zat aditif, lembar observasi aktivitas peserta didik, LKPD, soal tes dan angket tanggapan peserta didik terhadap pendekatan SETS. Hasil penelitian ini adalah Pemahaman awal peserta didik tentang zat aditif masih dalam kategori rendah khususnya sub topik pada ciri-ciri zat aditif. Hasil rata-rata observasi aktivitas peserta didik secara keseluruhan sebesar 80,5%. Kesimpulan dari Hasil penelitian ini adalah menunjukkan hasil ketuntasan belajar peserta didik sebesar 87,62%.. Hasil tanggapan peserta didik secara klasikal positif terhadap proses belajar-mengajar dengan penerapan pendekatan SETS sebesar 85,03%.Kata kunci: hasil belajar, zat aditif, pendekatan SETS, makanan.